Prevalence Of Energy Drinks Consumption Among Students Of Alkindy Medical College - Mohsin, Talib S. (AL-Kindy College Medical Journal, 2016)
Background: Energy drinks are non alcoholic beverages which contain stimulant drugs chiefly caffeine and marketed as mental and physical stimulators. Consumption of energy drinks is popular practice among college students as they are exposed to academic stress. Caffeine which is the main constituent of energy drinks could become an addictive substance or cause intoxication. Objectives: This study aims to assess the prevalence of energy drinks consumption among medical students of alkindy college of Medicine.Type of the study: A cross sectional study.Methods: It was performed at alkindy medical college on March 2016. A total number of 600 students were contacted to participate in this study. A self administered questionnaire was used to collect the data. Spss version 18.0 was used for statistical analysis.Results: Out of 600 students, 501 (83.5%) participated in the study. The majority were females 304 (60.7%) and only 197 (39.3%) were males with a mean age of (20.43 ± 1.74). 120 (24%) of participants had consumed energy drinks at least once. Higher proportion of male students 77 (64%) consumed energy drinks compared to females 43 (36%). Regarding inspiration of first use of energy drinks, the highest percentage 9.8% was due to friends. Majority of consumers 85 (17.2%) used energy drinks irregularly. The main cause of energy drinks consumption was focusing for studying 7.2% (n=36). Conclusions: Energy drinks consumption is a common practice among medical students. Friends had a strong influence on usage of energy drinks. Students consumed energy drinks mainly for focusing for studying. Further studies are recommended to evaluate factors involved in consumption of these drinks among medical students and their understanding of the risks involved as well as possible interventions to promote safe consumption